The elements of polymer science and engineering - Rudin, Alfred (Academic, 2013)
Whether you are an upper or graduate level student studying polymer science and engineering or an engineer new to the field of polymers, you'll benefit from reading The Elements of Polymer Science and Engineering 3e. Since the publication of the second edition in 1999, the field of polymers has advanced considerably. A key feature of the third edition is the inclusion of new concepts in existing chapters as well as new chapters covering selected contemporary topics such as behavior of natural polymers, polymer nanocomposites, and use of polymers in nanotechnology. There are also several enhancements to the book's pedagogy, including the addition of numerous worked examples and new figures to better illustrate key concepts and the addition of a large number of end-of-chapter exercises, many of which are based on recently published research and relevant industrial data. Hallmark features: Focuses on applications of polymer chemistry, engineering, and technology Explains terminology, applications, and versatility of synthetic polymersConnects polymerization chemistry with engineering applicationsContains practical lead-ins to emulsion polymerization, viscoelasticity, and polymer rheology.